Monitoring as an instrument for learning in Anatomy and Vegetable Ecophysiology in Licensing courses in Agricultural Sciences and Bachelor in Agroecology (Research, Society and Development, 2021)
The present work aims to report the monitoring experience lived in the discipline of Vegetal Anatomy and Ecophysiology offered in the undergraduate courses of CCHSA/UFPB, Degree in Agrarian Sciences and Bachelor in Agroecology, as well as to analyze the satisfaction and perception of students regarding the monitoring offered in these two courses. This work was divided into two parts: the first refers to the experience report lived by the monitors and the second about the perception that the students had in relation to monitoring in this discipline, through the application of a questionnaire. Monitoring activities in the discipline of Plant Anatomy and Ecophysiology played an extremely important role in improving learning within the classroom, as it contributed to a better understanding of the contents covered, in addition to providing the student-teacher exchange and theoretical deepening by part of the monitors. Monitoring has helped us to establish our vocation for the classroom, contributing to mutual learning and in a pleasant way with our fellow students. The monitoring allowed the monitor student to go deeper into the contents of the discipline, in addition to placing it close to the teacher, allowing a better understanding of the dimensions of teaching-learning, its gratifications and difficulties, in addition to allowing us to experience the face-to-face and remote monitoring. Thus, monitoring served to further strengthen the desire for teaching and the skills required for such an exercise.